Pengaruh literasi digital terhadap kemampuan guru dalam mengoperasikan aplikasi rapor digital sekolah dasar - Kumalasari, Fatmawati; Riyadi, Riyadi; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2023)
The purpose of this study is to determine whether or not there is an influence of digital literacy on teachers' ability to operate the digital report card application for elementary schools in Musuk District. This study is a type of descriptive associative quantitative research. The study population was all elementary school teachers in Musuk sub-district. Sample selection using the Slovin formula with error rate 5%. Digital literacy data collection techniques for elementary school teachers and teachers' ability to operate digital report card applications were taken using questionnaires through Google Form media. The data analysis techniques used are prerequisite analysis tests and hypothesis tests. The results of the study explain that digital literacy affects teachers' skills in operating digital report card applications. This influence is positive where the contribution of digital literacy influence on teachers' ability to operate report card applications is 42%. The low coefficient of determination of 0.420 shows that digital literacy variables are not the only factor that affects teachers' ability to operate digital report card applications.Keywords: Digital Literacy, Teacher's ability to operate Application, Digital Report Card Application